First report of the pepper thrips Thrips parvispinus (Karny) in Costa Rica - Rodríguez Arrieta, Jesús Alexander (2025)
The accidental invasive insects pose a growing threat to agricultural productivity and food security worldwide. Objective: To report for the first time the pepper thrips Thrips parvispinus in Costa Rica. Methodology: Specimens were collected from May to October 2024 in commercial crops Capsicum annuum, Citrus sinensis, Coriandrum sativum, Cucumis sativus, and ornamental Croton spp. in the western region of the country, encompassing both protected environments and greenhouses. The thrips identification was carried out using external morphological characteristics and partial sequencing of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Results: Morphological and molecular analyses confirmed the species identity of T. parvispinus. Implications: The observed damage included feeding scars on young leaves, margin curling, necrosis of foliar tissue, and floral deformation; with relevant implications for the health of these crops in Costa Rica. Conclusion: The detection of this invasive species represents a phytosanitary concern in Central America and underscores the necessity for continuous monitoring and implementation of effective insect management strategies throughout the region.